Retroauricular Graft as a Management of Simple Kissing Nevus in a Young Woman : a Case Report: Poster Presentation - Case Report - Ophthamologist - NI MADE LIENDERI WATI (Majalah Oftalmologi Indonesia, 2023)
Introduction : Kissing nevus is a rare case. The existence of this kissing nevus often causes disturbances not onlyof function but also cosmetic for the patient. This case report aims to report the surgical management of a simple kissing nevus that occurred in a young woman. Case Illustration : A 27 years old woman came to the ophthalmology department of Karangasem Hospital with complaint of visual disturbances and blackish mass growth on lateral aspect of upper and lower eyelids of left eye since birth. She underwent surgery to excise the mass. Eyelid reconstruction was carried out using a retroauricular graft. Discussion : Most cases of kissing nevus are usually present at birth. Eyelid reconstruction after kissing nevus excision can be a challenge for the surgeon to achieve functionally and cosmetically satisfactory results. In this case, eyelid reconstruction was chosen using retroauricular graft with the consideration that this technique is quite easy to do, the skin color is relatively similar, and the scar tissue behind the ears can also be hidden. Two months after surgery , the color of the graft is getting similar to the color of the surrounding skin, and the patient was quite satisfied with the results. Conclusion : Retroauricular graft can be an alternative graft for eyelid reconstruction after kissing nevus excision. It can provide quite satisfactory results functionally and cosmetically, especially for simple kissing nevus.